PERKEMBANGAN MORAL ANAK-REMAJA: COPY PASTE, PENDIDIKAN, ATAU KREATIVITAS? - Muchlisah, Muchlisah (Jurnal Biotek, 2013)
Moral is one of life device to using for recognize individual behavior so it can adjust with social rules. For that matter, moral can be signs and individual guidance. But in reality, not least from the individual behaviors does not reflect any moral content. Many cases of pornography, sexual immorality, and other unlawful to make an evaluation how the moral sense can be interpreted. How true moral function can be restored as moral reasons and why moral to set out in life. This is become important topic, because the moral course touches all aspects of life. The discussion here is a variation of moral development and investment that generates diversity in the application of moral behavior. Completely depends on the upbringing and education in formal schools that will determine how the individual from childhood to adolescence to make sense of morals. The conclusion of the discussion of moral featured version that is the result of moral development; moral as a result of copy paste, education, and or creativity.